2012
DOI: 10.1080/03602559.2012.679723
|View full text |Cite
|
Sign up to set email alerts
|

Isothermal Cure of Bisphenol Epoxy Resin with a Nonlinear Aliphatic Polyamine Hardener

Abstract: An amine terminated polypropylenimine dendrimer (DABdendri-(NH 2 ) 4 ), was employed as a new nonlinear aliphatic curing agent for diglycidyl ether of bisphenol A (DGEBA). Isothermal curing reaction kinetics of DGEBA/DAB was investigated with a differential scanning calorimeter (DSC). The autocatalytic model proposed by Kamal was demonstrated for simulating the reaction kinetic in the initial stage of the cure. It was found that the overall reaction order, m þ n, was in the range 2.3688-2.5980. The rate consta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…More generally, the reaction kinetics of bisphenol-A epoxy resins cured with polyamido-amine dendrimers has been studied [11,12], and it has been reported that, in comparison with the use of EDA as curing agent, the curing kinetics using polyester-amine dendrimers is very different, presenting two stages of cure and less heat of reaction [13]. The use of polypropylene-imine dendrimers as curing agents in epoxy systems is quite widely reported [14,15,16], and it appears that the molecular architecture of the dendrimers, in particular their steric hindrance and the number of attached –OH groups [14], greatly affects the reaction kinetics. It is clear that suitable dendrimers can effectively crosslink epoxy resins, and this may be advantageous if the dendrimers exhibit improved compatibility with epoxy resins over the conventional linear aliphatic amine curing agents of low molecular weights.…”
Section: Introductionmentioning
confidence: 99%
“…More generally, the reaction kinetics of bisphenol-A epoxy resins cured with polyamido-amine dendrimers has been studied [11,12], and it has been reported that, in comparison with the use of EDA as curing agent, the curing kinetics using polyester-amine dendrimers is very different, presenting two stages of cure and less heat of reaction [13]. The use of polypropylene-imine dendrimers as curing agents in epoxy systems is quite widely reported [14,15,16], and it appears that the molecular architecture of the dendrimers, in particular their steric hindrance and the number of attached –OH groups [14], greatly affects the reaction kinetics. It is clear that suitable dendrimers can effectively crosslink epoxy resins, and this may be advantageous if the dendrimers exhibit improved compatibility with epoxy resins over the conventional linear aliphatic amine curing agents of low molecular weights.…”
Section: Introductionmentioning
confidence: 99%